Urinary Kidney Injury Molecule-1 (KIM-1) in Early Diagnosis of Acute Kidney Injury in Pediatric Critically Ill - Paramastuty, Irma Lestari; Soebandiyah, Krisni; Purnomo, Basuki B. (Journal of Tropical Life Science, 2016)
Acute kidney injury (AKI) often associated with a high hospital morbi-mortality rate in the intensive care unit patients. Kidney injury molecule-1 (KIM-1), has many characteristics of ideal biomarker for kidney injury. The aim of this study was to compared the temporal pattern of elevation urinary KIM-1 level following critically ill children with SCr as standart biomarker of AKI. Prospective analytic observational study was conducted during October to March 2014 in the Saiful Anwar General Hospital and Physiology Laboratory Brawijaya University. There were 13 critically ill as subjects. SCr and KIM-1 levels from all subjects were measured three times ( at admission, after 1st and 6th hour). Subjects were devided into AKI - non-AKI groups by SCr level and survivor - non survivor group at the and of the observations. Results showed that there were significantly increased levels of KIM-1 in the AKI and non-AKI and survivor-non survivor group at time point. However, we found that delta KIM-1 at time point increased significant in non AKI group and survivor group. KIM-1 at admission can diagnosed AKI in critically ill children. We conclude that urinary KIM-1 is a sensitive non-invasive biomarker to diagnosed acute kidney injury in critically ill children. Increase level of KIM-1 by time shows protective and good outcome in critically ill children.